Faktor-Faktor Yang Berhubungan Dengan Pemberian Vitamin A Pada Balita di Posyandu Flamboyan Wilayah Kerja Puskesmas Rawasari - Ambo Sengeng (Poltekkes Kemenkes Jambi, 2016)
Vitamin A is a fat-soluble vitamin found first. Vitamin A is essential for maintaining thehealth and survival. Around the world in preschool children is estimated there are around 6-7million new cases of vitamin A deficiency every year, approximately 10% of them suffer fromcorneal damage. Vitamin A deficiency is the leading cause of blindness is most often found inchildren and make 250000-500000 children become blind each year, and half of them will diewithin the year. Approximately another 150 million children face an increased risk of death inchildhood due to an infectious disease caused by vitamin A status is not adequate.The purpose of this study to determine the factors associated with the provision ofvitamin A in Toddlers in Posyandu Flamboyan eorking area ofPuskesmas Rawasari.Desain iscross sectional study. Population and sample are mothers who have children under five in SubFlamboyan IHC Rawasari totaling 53 people. The sampling technique total sampling. Dataanalysis is done in stages, namely univariate and bivariate.The results showed that 77.4% of respondents have a good behavior by giving vitamin Atoddler on schedule, 52.8% of respondents have good knowledge about vitamin A in infants,54.7% of respondents have a good perception of the administration of vitamin A in infants,56.6% of respondents have a high motivation in giving vitamin A in young children, there is asignificant relationship between knowledge by administering vitamin A in infants seen from pvalue of 0.047, there is a significant relationship between the perception by giving vitamin A ininfants views of p- value of 0.024 and there is a significant relationship between motivation andthe provision of vitamin A in infants seen from p-value of 0.019.